UTILIZING MULTIFUNCTIONAL BOARD MEDIA TO IMPROVE STUDENT LEARNING OUTCOMES IN GRADE IV AT MIN 26 ACEH BESAR - Narfi, Muhammad Afif; Jarmita, Nida; M. Daud, Ridhwan (PIONIR: JURNAL PENDIDIKAN, 2024)
The use of appropriate media is a way to overcome and minimize low student achievement. Mathematics is a subject that will certainly feel difficult if taught monotonously. Preliminary study results on March 6, 2023, showed that learning outcomes in class IV-A at MIN 26 Aceh Besar were still low, as indicated by only 6 students (21%) out of 28 achieving scores above 73. Thus, the difficulty of mathematics can be used as a benchmark for low student achievement. This study used Classroom Action Research (CAR) with three cycles, each consisting of four stages: planning, implementation, observation, and reflection. Data was collected through observation and testing, then analyzed using percentage formulas. The instruments used in this study were observation sheets and tests. The results showed an improvement: before entering the cycles, a diagnostic test was conducted with a score of 10.71%, followed by Cycle I with a score of 75%, increasing to 85.71% in Cycle II, and further increasing to 89.28% in Cycle III. Finally, a post-test was conducted, yielding a score of 92.85%. Teacher activity scored 68.18% in Cycle I, increased to 77.08% in Cycle II, and further increased to 87.5% in Cycle III. Student activity results were 60% in Cycle I, increased to 70.90% in Cycle II, and increased to 86.81% in Cycle III. Ultimately, it can be concluded that the use of multifunctional board media can improve student learning outcomes in grade IV.Keywords: Multifunctional Board Media, The Learning Outcomes.